2017
DOI: 10.1016/j.cmi.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vancomycin minimum inhibitory concentration on the outcome of methicillin-susceptible Staphylococcus aureus left-sided infective endocarditis treated with antistaphylococcal β-lactam antibiotics: a prospective cohort study by the International Collaboration on Endocarditis

Abstract: Objectives Left-sided methicillin-susceptible Staphylococcus aureus (MSSA) endocarditis treated with cloxacillin has a poorer prognosis when the vancomycin minimum inhibitory concentration (MIC) is ≥1.5 mg/L. We aimed to validate this using the International Collaboration on Endocarditis cohort and to analyse whether specific genetic characteristics were associated with a high vancomycin MIC (≥1.5 mg/L) phenotype. Methods All patients with left-sided MSSA infective endocarditis treated with antistaphylococca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
7
2
1
Order By: Relevance
“…In contrast, a longitudinal, prospective, multicenter study of MRSA endocarditis found no association of vancomycin MIC ≥1.5 μg/mL with higher mortality, although it was related to a greater persistence of bacteremia and a higher frequency of sepsis/septic shock, peripheral embolism, and arthritis/osteomyelitis [35]. Likewise, a study on beta-lactamtreated left-sided MSSA endocarditis found no relationship between vancomycin MIC and mortality or microorganism virulence [36]. The mortality rate of S. aureus endocarditis was very high in our cohort, despite the receipt of antibiotic treatment that accorded with antibiogram results and was recommended in available clinical practice guidelines by 90% of the patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, a longitudinal, prospective, multicenter study of MRSA endocarditis found no association of vancomycin MIC ≥1.5 μg/mL with higher mortality, although it was related to a greater persistence of bacteremia and a higher frequency of sepsis/septic shock, peripheral embolism, and arthritis/osteomyelitis [35]. Likewise, a study on beta-lactamtreated left-sided MSSA endocarditis found no relationship between vancomycin MIC and mortality or microorganism virulence [36]. The mortality rate of S. aureus endocarditis was very high in our cohort, despite the receipt of antibiotic treatment that accorded with antibiogram results and was recommended in available clinical practice guidelines by 90% of the patients.…”
Section: Discussionmentioning
confidence: 93%
“…The mortality from SA in our cohort was associated in bivariate analyses with: the decade of endocarditis onset (1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999): mortality rate of 20.3% (37/182) vs. survival rate of 12.5% (28/224), p = 0.032; 2000-2010: 42.8% (78/ 182) vs. 36.8% (67/224), p = 0.007; 2010-2017: 36.8% (67/182) vs 57.6% (129/224); p = 0.0001); older age (61.5 vs. 56.4 years; p = 0.004); active neoplasm (11.2 vs. 5.8%; p = 0.05); early prosthetic IE (9.4 vs. 4%; p = 0.028); mitral valve involvement (64.6 vs. 49.5%; p = 0.03); sepsis/ septic shock (46.7 vs. 27.8%; p = 0.0001); kidney failure during IE episode (52.2 vs. 33.9%; p = 0.0001); de novo heart failure (60.2 vs. 33.8%; p = 0.0001); CNS involvement (encephalopathy 37.6 vs. 22.6%; p = 0.006; embolic stroke 29.6 vs. 18.7%; p = 0.033; meningitis 8.9% vs 5.8%; p = 0.035); high surgical risk (median EuroSCORE of 13 vs. 9; p = 0.0001; median logistic EuroSCORE of 30.76 vs. 15.4; p = 0.0001; and indication but non-performance of surgery (16.5 vs. 4.9%; p = 0.0001). MRSA itself did not emerge as a risk factor for mortality in our cohort (29% vs. 11.8%, p = 0.22) Protective factors were: IE on pacemaker lead or automatic implantable cardioverterdefibrillator (AICD) (2.8 vs. 12.9%; p = 0.0001); osteoarticular spread of the infection (9.6 vs. 17.3%; p = 0.026); heart surgery conducted when indicated without delay (23.1 vs. 36.2%; p = 0.004).…”
Section: Risk Factors Associated With Mortality From Samentioning
confidence: 96%
“…If such is the case, these findings will be of increasing importance given the temporal trends in vancomycin MICs in MSSA and the slow declines in the fraction of disease caused by MRSA. It is worth acknowledging, however, that other investigators examining this issue have not found a consistent relationship between vancomycin MIC and clinical outcome in invasive staphylococcal infection (31,32). Such discrepancies in the literature might be a consequence of variability in MIC methodologies (33), definitions of primary outcomes, and/or global variability in strain types or intrinsic virulence.…”
Section: Discussionmentioning
confidence: 94%
“…The details regarding identification of relevant studies are shown in figure 1 . Two studies 17 26 contained duplicate patients and the study with smaller sample size 26 was excluded.…”
Section: Resultsmentioning
confidence: 99%
“… 34 MSSA isolates with genotypes spa -002 and spa -CC008 correlate with an elevated vancomycin MIC, 24 and isolates with extracellular fibrinogen binding protein and serine endopeptidase are associated with a higher incidence of embolism. 26 …”
Section: Discussionmentioning
confidence: 99%